THE INTERSECTION OF CORPORATE SOCIAL RESPONSIBILITY AND INNOVATION: A CATALYST FOR SUSTAINABLE GROWTH - Lucya Erlinda Sonia; Basuki (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
The intersection of Corporate Social Responsibility (CSR) and innovation has garnered significant attention in recent years, as organizations increasingly recognize the potential of CSR initiatives to drive innovative practices. This literature review explores how integrating CSR into business strategies not only enhances corporate reputation, but also fosters creativity and sustainable growth. Research indicates that CSR can act as a catalyst for innovation by aligning organizational goals with social and environmental objectives. By measuring the impact of CSR efforts through key performance indicators, organizations can effectively communicate their results, enhancing credibility and stakeholder relations. This article accentuates the importance of stakeholder engagement in driving innovation through CSR. Collaborative platforms, such as Unilever's Open Innovation Portal, Tesla, etc., have proven effective in harnessing external expertise and driving innovation. It concludes by emphasizing the powerful relationship between CSR and innovation as a driver of competitive advantage. By embracing CSR as a strategic imperative, organizations can unlock new opportunities, foster collaboration, and build a sustainable future. As businesses move forward, it is crucial to integrate CSR into their core strategies, leveraging the power of innovation to create positive social and environmental impact while driving business success.